Individual magnetic resonance imaging and radiographic features of knee osteoarthritis in subjects with unilateral knee pain: the health, aging, and body composition study. - Javaid, M; Kiran, A; Guermazi, A; Kwoh, C; Zaim, S; Carbone, L; Harris, T; McCulloch, C; Arden, N; Lane, N; Felson, D; Nevitt, M (2012)
OBJECTIVE: Strong associations between radiographic features of knee osteoarthritis (OA) and pain have been demonstrated in persons with unilateral knee symptoms. This study was undertaken to compare radiographic and magnetic resonance imaging (MRI) features of knee OA and assess their ability to discriminate between painful and nonpainful knees in persons with unilateral symptoms. METHODS: The study population included 283 individuals ages 70-79 years with unilateral knee pain who were enrolled in the Health, Aging, and Body Composition Study, a study of weight-related diseases and mobility. Radiographs of both knees were read for Kellgren/Lawrence (K/L) grade and individual radiographic features, and 1.5T MRIs were assessed using the Whole-Organ Magnetic Resonance Imaging Score. The association between structural features and pain was assessed using a within-person case-control design and conditional logistic regression. Receiver operating characteristic (ROC) analysis was then used to test the discriminatory performance of structural features. RESULTS: In conditional logistic analyses, knee pain was significantly associated with both radiographic features (any joint space narrowing grade ≥ 1) (odds ratio 3.20 [95% confidence interval 1.79-5.71]) and MRI features (any cartilage defect scored ≥ 2) (odds ratio 3.67 [95% confidence interval 1.49-9.04]). However, in most subjects, MRI revealed osteophytes and cartilage and bone marrow lesions in both knees, and using ROC analysis, no individual structural feature discriminated well between painful and nonpainful knees. The best-performing MRI feature (synovitis/effusion) was not significantly more informative than K/L grade ≥ 2 (P = 0.42). CONCLUSION: In persons with unilateral knee pain, MRI and radiographic features were associated with knee pain, confirming that structural abnormalities in the knee have an important role in the etiology of pain. However, no single MRI or radiographic finding performed well in discriminating between painful and nonpainful knees. Further work is needed to examine how structural and nonstructural factors influence knee pain.